Legal Protection for Owners of Well-Known Trademarks from the Perspective of Court Decisions - Rini B. A. Silitonga; Hulman Panjaitan; Paltiada Saragi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
Protection of well-known trademarks is a crucial aspect of intellectual property systems, especially in the face of global trade dynamics and the development of digital technologies. This study aims to analyze the effectiveness of legal protection for owners of well-known trademarks from the perspective of court decisions in Indonesia. Using a qualitative method based on a normative juridical approach and case studies of court rulings (including the Hugo Boss and Superman cases), this research reveals that trademark protection in Indonesia remains reactive, dependent on litigation, and has not fully prevented the registration of confusingly similar trademarks by parties acting in bad faith. Moreover, the absence of objective standards for defining well-known trademarks and indicators of bad faith weakens legal certainty. On the other hand, courts have begun to show consistency in rejecting trademark registrations that violate the principles of well-known trademark protection, although this has yet to be supported by an adequate administrative system from the Directorate General of Intellectual Property (DJKI). The study recommends the establishment of technical regulations, strengthening DJKI’s capacity, and integrating protection systems with international norms as strategic steps to reinforce legal protection for owners of well-known trademarks in Indonesia.